Effects of intrinsic and extrinsic factors on the diet of a bentophagous skate - Barbini, Santiago Aldo (2013)
The effects of intrinsic (sex, maturity stage and body size) and extrinsic (depth and region) factors on the diet of Bathyraja macloviana, in the south-west Atlantic Ocean, were evaluated using a multiple-hypothesis modelling approach. Bathyraja macloviana fed mainly on polychaetes followed by amphipods, isopods and decapods. Effects of intrinsic and extrinsic factors on diet composition of this species were found. The consumption of polychaetes had a humped relationship with total length (LT), and isopods and decapods increased with increasing LT. Immature individuals preyed on amphipods more heavily than mature individuals. Furthermore, region and depth had an important effect on the consumption of isopods, decapods and amphipods. Such ontogenetic changes and spatial patterns may provide insights into understanding the regulatory mechanisms of marine communities.